Habitat use between two sympatric species of squirrels (Sciurus aureogaster and Sciurus deppei) in a tropical rainforest in Los Tuxtlas, Veracruz, Mexico - Rojas Sánchez, J. Vladimir; Coates, Rosamond; Sánchez-Cordero, Víctor; Flores-Martínez, José Juan (Therya Notes, 2025)
The coexistence of species depends on niche partitioning for food and space. Among related species, competition may be higher since similar needs drive homologous traits. Studying these processes offers insights into factors that contribute coexistence. Since human-modified landscapes increase environmental differences, we expected the sympatric squirrels Sciurus aureogaster and Sciurus deppei to exhibit differences in their associations with habitat characteristics. We set 21 camera traps in the canopy of a rainforest at the Los Tuxtlas Tropical Biology Station from August 2022 to October 2024. Environmental and vegetation variables were included, and spatial variations in the number of records were analyzed according to three zones (Z1, Z2, and Z3). A Principal Component Analysis (PCA) was performed to detect spatiotemporal responses of both species. A total of 594 species-level squirrel records were differentially obtained across zones: S. aureogaster was more frequent in Z1, while S. deppei dominated in Z3. Although more records occurred in the rainy season, no statistically significant differences were found. The PCA showed that all environmental variables were related to squirrels, with distinct species-specific associations across survey years. Squirrel species were relatively frequent at the site, showing high spatiotemporal variation. Vertical space use may be a component favoring spatial segregation, as S. deppei occupies both canopy and understory, while S. aureogaster is strictly arboreal. No seasonal effects were observed in capture frequency, though interannual variation occurred in relation to environmental variables.